Exploring plant polyphenols as anti-allergic functional products to manage the growing incidence of food allergy - Wu, Tianxiang; Li, Zhenxing; Wu, Yanyan; Yang, Xianqing; Li, Laihao; Chen, Shengjun; Qi, Bo; Wang, Yueqi; Li, Chunsheng; Zhao, Yongqiang (Frontiers in Nutrition, 2023)
The active substances derived from plants have received increasing attention owing to their wide range of pharmacological applications, including anti-tumor, anti-allergic, anti-viral, and anti-oxidative activities. The allergy epidemic is a growing global public health problem that threatens human health and safety. Polyphenols from plants have significant anti-allergic effects and are an important source of anti-allergic drug research and development. Here, we describe recent advances in the anti-allergic efficacy of plant polyphenols, including their comprehensive effects on cellular or animal models. The current issues and directions for future development in this field are discussed to provide a theoretical basis for the development and utilization of these active substances as anti-allergic products.